First Light and Beyond Making a Success of Astronomical Observing - Jenkins, D. A. (The Patrick Moore Practical Astronomy Series, 2015)
Amateur astronomers who have been disappointed by the results of an observing session can still gain useful experience in a seemingly "failed" night at the telescope. In a world with imperfect seeing conditions, incredible observing sessions are often mixed with less inspiring ones, discouraging the amateur observer. This book is designed to help novice observers take something worthwhile away each and every time they go out under the night sky, regardless of what was originally planned. Almost every observer remembers his first sight of Ringed Saturn, hanging majestically in the blackness of space. Practitioners agree that visual observing is special. Real-time observations at the eyepiece can provide fleeting yet intense feelings that connect us with the universe. But when expectations aren't met at the eyepiece, there are other ways to profit from the practice of astronomy. These rewards, though less showy, are well worth cultivating. This book will help you see what constitutes a "successful" visual observing session. It explains the nature of the objects you are seeing and advises how best to use your equipment. There are many hints and tips about how best to locate, recall, and record observations, including suggestions for trips to dark sky areas and to public observatories. Amateur astronomy is a journey from the urban backyard all the way to dark rural skies. With this guide the journey can be smooth.